DETERMINATION OF THE PRIORITY SCALE FOR THE LOCATION OF THE LABOR INTENSIVE PROGRAM AT THE MANPOWER AND TRANSMIGRATION OFFICE OF MALAKA REGENCY - Vinsensius Babu; William Djani; Ajis Salim Adang Djaha (Postgraduate School, Universitas Nusa Cendana, 2022)
Decision making is an activity that can be carried out by anyone in his position as what and for what. Decisions are very important when it comes to the life or interests of many people. This was also experienced by the Malacca Regency Manpower and Transmigration Office in determining the location of the Labor Intensive Program. The Infrastructure Labor Intensive Activity is a community empowerment activity aimed at: reducing the number of unemployed, underemployed and the poor; fostering a sense of community and community cooperation; increasing community accessibility to basic social service centers; and increase the quality and quantity of community development towards a better direction. So far, the determination of labor-intensive locations has not had a standard standard so that it often creates jealousy between villages and the emergence of a public perception that the location of labor-intensive programs is based on the subjective assessment of officials from the Manpower and Transmigration Office. This study aims to determine what criteria are used in determining the priority scale of labor-intensive program locations in Malacca Regency; What types of infrastructure development programs will be carried out in Malacca Regency; and Determining the priority scale for the location of labor-intensive infrastructure programs in Malacca District. This research consisted of 15 informants and was carried out for 1 month at the Manpower and Transmigration Office of Malacca Regency.The research found that there were several criteria in determining the priority scale for labor-intensive locations in Malacca Regency, including: Number of beneficiaries (unemployed, underemployed, full PMI, victims of layoffs, the poor, CMPI who failed to leave due to COVID-19, and PMI who returned home. because the country is placing a lockdown); potential for community economic improvement; and support for natural resources and labor resources). Types of infrastructure labor-intensive programs in Malacca District include: Clean Water Network Development; Environmental Road (Pavement Construction); Environmental Road Construction (Construction Rebates); Farming Business Road Development; Polindes Development; Irrigation Development; and Drainage Development.